Analysis of three ice melting methods in supercooled water ice-making system. (1st August 2023) - Hu, Rui; Zhang, Xuelai
Abstract: In supercooled water ice-making system, ice jam threatens the stability of the system. In order to make the sub-cooler melt the ice on the pipe wall in time when the ice jam is about to happen, three methods of ice melting are put forward. The energy analysis, exergy analysis, economic analysis and carbon emission analysis were carried out for the three ice-melting methods. The results showed that the heat loss was zero, the energy utilization efficiency was the highest, and the carbon dioxide emission was the lowest when the ice-melting method of heat storage was used, running cost minimum, of each ice-melting only 0.103 yuan. The exergy loss of reverse method is 18.93 kJ/kg, but the reverse method has the highest melting temperature and the shortest melting time. The bypass method has a heat loss of 106.11 kJ/kg. The cost of melting ice and carbon dioxide emission is higher than the other two methods, but the initial investment is the lowest and the system is the most compact. Highlights: Three ice melting methods are proposed. The efficiency of the three methods is analyzed from multiple angles. Carbon emission analysis is added.